The perception of micro-entrepreneurs and petty traders on conventional and Islamic microfinance: a case study of Pakistan - Abbas, Kausar; Abdul Razak, Dzuljastri; Md Saad, Norma (IIUM Institute of Islamic Banking and Finance, 2014)
Microfinance is a general term that entails the provision of financial services to micro-entrepreneurs or to those who do not have access to banking facilities. The current issues faced by micro-entrepreneurs are difficulties in seeking financing from financial institutions due to lack of sufficient collateral, no credit history, irregular or uneasily verified sources of income. Consequently, they often rely on relatives or local moneylenders who charge high interest rates.Thus, on grounds of equity and justice, Islamic microfinance seems to provide an alternative needed by them. This research deals with the perceptions of micro-entrepreneurs and petty traders towards conventional and Islamic microfinance in Pakistan. It further investigates the intention to use Islamic microfinance and challenges for the micro-entrepreneurs. A total of 270 people were surveyed by means of self- administered questionnaire. The sample comprises 81 percent males and 19 percent females in three major cities; Rawalpindi, Lahore and Peshawar. Results of this study indicate that Islamic microfinance is a preferred choice as compared to conventional microfinance and best answer to poverty eradication. Although, Islamic microfinance is a new concept but majority of respondents had some understanding of this concept. However, the respondents also expressed their dissatisfaction to the management of Islamic banks.